Citizenship education after Ukraine: Global citizenship education in a world of increasing international conflict - Borgebund, Harald; Børhaug, Kjetil (JSSE - Journal of Social Science Education, 2024)
Highlights: Global citizenship struggles to make sense of recent developments in international politics, such as the Ukraine war. Theories of international politics offer tools to make sense of the current international situation. Global citizenship ought to provide a comprehensive understanding of the international situation. Didactical implications of broadening the perspective of global citizenship. More research is required on the didactical implications. Purpose: Following globalisation, a rich literature on global citizenship education developed (Akkari & Maleq 2020; Goren & Yemini 2017). However, recent developments in international politics prompt us to ask whether global citizenship education gives young people a grasp of the international world. We argue that global citizenship education theory must be supplemented because it does not provide much guidance to help young people understand international politics properly. Design/methodology/approach: We discuss how theories of global citizenship education conceptualise international conflicts and how three theories on international politics offer supplementary conceptions and perspectives. Findings: Global citizenship education should be supplemented with theories of international politics. Research limitations/implications: Our analysis only indicates some implications for global citizenship education, and further research on the didactical implications is required. Practical implications: Global citizenship education must rely on a wider set of theories to prepare the students for understanding global issues.